PHYSICAL THERAPY AFTER HIP FRACTURE (Physical Culture and Sport: Scientific Perspective, 2023)
With the increase in the proportion of elderly people in the population, the frequency of hip fractures increases, mainly in 90% of cases, this fracture occurs precisely in people of the older age group. In this category of the population, the treatment of trauma is a serious problem, as severe complications are noted (in 25–30%), a complex and long recovery period, and high mortality. In our country, up to 24% of patients die within a year after an injury, and more than 50% become disabled, while this indicator does not decrease. Orthopedic surgeons have traditionally focused on the surgical treatment of hip fractures, but in recent years there has been a growing awareness of the importance of postoperative rehabilitation. The purpose of the study is to summarize the latest recommendations for the rehabilitation of patients with hip fractures after surgical interventions, which can be carried out during hospitalization and after discharge. Research methods. Theoretical research methods were used in the work: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature. Results. Many studies have shown that adequate rehabilitation after hip fracture surgery can reduce hospital stay and improve clinical outcomes. Quantitative assessment of preoperative and postoperative independence is necessary for an objective assessment of recovery. Measurement of preoperative activity indicators and their comparison with postoperative follow-up indicators can help predict functional outcomes of postoperative rehabilitation. Conclusions. Postoperative rehabilitation may improve clinical outcomes and quality of life in patients with hip fracture, but due to the variety of study methods and differences in the results of published studies, there are insufficient data to conclusively support this potential benefit. It is critical for the physical therapist to apply individualized approaches to patient rehabilitation and to understand the potential strengths and weaknesses of different intervention options
Keywords: fracture; femur; physical therapy; endoprosthesis; old age